A generic topography reconstruction method based on multi‐detector backscattered electron images. (29th May 2022) - Neggers, Jan; Héripré, Eva; Bonnet, Marc; Hallais, Simon; Roux, Stéphane
Abstract: Surface topographies can be reconstructed from backscattered electron (BSE) images captured from different detector orientations. This article presents a very general approach to this problem, in the spirit of photometric stereo methods, allowing for arbitrary BSE detector number (at least 3) and shapes. The general idea is to both determine the (non‐linear) model parameters and compute the surface topography so that the modelled images match at best the acquired ones. Three samples are used for validation of the measured topography with respect to atomic force microscopy (AFM) measurements. Root mean square (RMS) errors in the range of 10–35 nm, or 1–1.5% of total sampleheight, are obtained.